Modern Trends In Preparing Students For Speech Therapy Activities In Inclusive Education - Sharifova, Maxliyo (TLEP – International Journal of Multidiscipline, 2026)
This article explores the modern trends and pedagogical conditions necessary for preparing future speech therapists to work effectively within inclusive educational environments. As inclusive education becomes a global priority, traditional methods of correctional pedagogy must be supplemented by innovative approaches, including digital didactic tools, interactive methodologies, and modernized practical training. The study analyzes the critical need to update higher education curricula to foster both the professional and digital competencies of students majoring in special pedagogy. Particular attention is given to the practical application of these modern trends in early childhood and preschool education settings, where early intervention and individualized approaches are crucial. By integrating theoretical knowledge with practical skills in utilizing modern educational technologies, universities can produce highly qualified, adaptable specialists capable of designing effective correctional pathways for children with diverse special educational needs. The findings suggest that a modernized training framework significantly enhances the professional readiness, psychological adaptability, and pedagogical effectiveness of future speech therapists in inclusive classrooms.